2014
DOI: 10.1039/c3tb21338b
|View full text |Cite
|
Sign up to set email alerts
|

Highly crystallized iron oxide nanoparticles as effective and biodegradable mediators for photothermal cancer therapy

Abstract: We report that highly crystallized iron oxide nanoparticles (HCIONPs) made by thermal decomposition and further coating with a polysiloxane-containing copolymer can be used as effective mediators for photothermal therapy. Irradiation of a HCIONP solution containing 0.5 mg mL À1 Fe, for instance, with an 885 nm diode laser at a power of 2.5 W cm À2 , induces a temperature increase of 33 C from room temperature, while water produced only a $3 C increase as the control. In vivo studies are further evaluated for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
97
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(107 citation statements)
references
References 47 publications
7
97
1
Order By: Relevance
“…Indeed, Sun and co-workers reported fabricating highly crystalline iron oxide NPs (24 nm) via thermal decomposition, which were then coated with a polysiloxane-containing copolymer for effective photothermal ablation. 70 The authors also evaluated the highly crystalline iron oxide NPs combined with an 885 nm laser at a power of 41 W cm − 2 in an in vitro system and in SUM-159 tumorbearing mice. Despite these successful results, most reported synthesized Fe 3 O 4 NPs possess a nonstoichiometric structure and do (Figure 7a).…”
Section: Fe 3 O 4 Nanostructuresmentioning
confidence: 99%
“…Indeed, Sun and co-workers reported fabricating highly crystalline iron oxide NPs (24 nm) via thermal decomposition, which were then coated with a polysiloxane-containing copolymer for effective photothermal ablation. 70 The authors also evaluated the highly crystalline iron oxide NPs combined with an 885 nm laser at a power of 41 W cm − 2 in an in vitro system and in SUM-159 tumorbearing mice. Despite these successful results, most reported synthesized Fe 3 O 4 NPs possess a nonstoichiometric structure and do (Figure 7a).…”
Section: Fe 3 O 4 Nanostructuresmentioning
confidence: 99%
“…The unique properties of iron oxide magnetic nanoparticles are suitable for using in biocatalysis and bioseparation areas 160 .…”
Section: Biomedical Applications Of Iron Oxide Npsmentioning
confidence: 99%
“…9,[12][13][14][15] Chen et al 14 reported that the highly crystallized iron oxide nanoparticles administered through the tail vein for PTT as effective and biodegradable mediators. These injected nanoparticles are likely to be applied for PTT as a result of the enhanced permeability and retention (EPR) effect and is cleared from the body through urinary excretion without long-term toxicity.…”
Section: Introductionmentioning
confidence: 99%